Inflammatory Bowel Disease A Point of Care Clinical Guide - Stein, Daniel J.; Shaker, Reza (Springer International Publishing : Imprint: Springer, 2015)
This volume provides a unique point-of-care reference for clinicians who care for Inflammatory Bowel Disease patients.  Busy clinicians need the best evidence based answers to patient questions at their fingertips at the time questions present themselves. Each chapter is based on responses to common IBD patient questions from IBD experts who answer these questions everyday.  Through these questions this book guides clinicians through the complicated management of IBD; including disease onset and natural history, therapy initiation, medications complications, therapeutic monitoring, surgery and accurate disease monitoring. Lastly, the book addresses special situations, such as alternative therapies, pregnancy, and fertility.    Written by experts in the field, Inflammatory Bowel Disease: A Point of Care Clinical Guide is a valuable reference for gastroenterologists, gastroenterology fellows, mid-level providers and any clinician involved in the care of IBD patients.